1996
DOI: 10.1128/aac.40.6.1366
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effect of antibiotics on cytokine production by human monocytes in vitro

Abstract: Some antimicrobial agents have been reported to modify the host immune and inflammatory responses both in vivo and in vitro. Fosfomycin (FOM) and clarithromycin (CAM) have immunomodulatory activity on human lymphocyte function. In the present study, we examined the effects of FOM and CAM on cytokine synthesis by lipopolysaccharide (LPS)-stimulated human monocytes in comparison with that of dexamethasone in vitro.The three drugs demonstrated positive or negative effects on the synthesis of various cytokines by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
103
0
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(113 citation statements)
references
References 21 publications
7
103
0
3
Order By: Relevance
“…When infected, in vivo macrophages are activated, and pro-inflammatory cytokines and anti-inflammatory cytokines are secreted from monocytes and other secretory cells; thus, an immunological homeostatic state can be maintained. [18,19] TNF-a and IL-1 are pro-inflammatory cytokines, which can trigger the overexpression of macrophages and monocytes to secret cytokines. [20] IL-6, IL-1 receptor antagonist IL-1ra, and IL-10 belong to the anti-inflammatory cytokines.…”
Section: Immunological Responses-elisa For Tnf-a and Il-6mentioning
confidence: 99%
“…When infected, in vivo macrophages are activated, and pro-inflammatory cytokines and anti-inflammatory cytokines are secreted from monocytes and other secretory cells; thus, an immunological homeostatic state can be maintained. [18,19] TNF-a and IL-1 are pro-inflammatory cytokines, which can trigger the overexpression of macrophages and monocytes to secret cytokines. [20] IL-6, IL-1 receptor antagonist IL-1ra, and IL-10 belong to the anti-inflammatory cytokines.…”
Section: Immunological Responses-elisa For Tnf-a and Il-6mentioning
confidence: 99%
“…13 In several recent studies, FOM was also shown to exert immunomodulatory effects on various immune cells by suppressing the production of inflammatory cytokines and chemokines, under both in vitro and in vivo conditions. [14][15][16][17] It still remains to be evaluated whether FOM affects the immune cells associated with any diseases.…”
Section: Introductionmentioning
confidence: 98%
“…[2][3][4] These soluble factors can initiate the innate immune phagocytic response and maintain the acute phase of the inflammation by the concurrent release of higher levels of proinflammatory cytokines, NO, free radicals, and lysosomal hydrolytic enzymes. 2 Inflammation states, tissue destruction, and systemic spread of the infection are established by these cellular processes through these chemical mediators, hydrolytic enzymes, and lipoxygenation.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Tumor necrosis factor (TNFα), interleukin 1 (IL-1), IL-6, and IL-8, are biologically active peptides produced by phagocytic macrophages, polymorphonuclear leukocytes (PMNs), eosinophils, and monocytes induced by the pathogen organisms, endotoxin, and other stimuli. [2][3][4] These soluble factors can initiate the innate immune phagocytic response and maintain the acute phase of the inflammation by the concurrent release of higher levels of proinflammatory cytokines, NO, free radicals, and lysosomal hydrolytic enzymes. 2 Inflammation states, tissue destruction, and systemic spread of the infection are established by these cellular processes through these chemical mediators, hydrolytic enzymes, and lipoxygenation.…”
Section: Introductionmentioning
confidence: 99%